Nine months a slave: when pregnancy is involuntary servitude to a foetus. Issue 52 (1st January 2018) - Allotey-Reidpath, Kiva Diamond; Allotey, Pascale; Reidpath, Daniel D
Abstract: Recent globally compiled evidence suggests that one-quarter of pregnancies end in abortions. However, abortions remain illegal in many countries, resulting in unsafe practices. Debates have largely stalled with the pro-life, pro-choice epithets. To provide further arguments in support of legalising abortion services, we argue that the state cannot demand of a woman that she maintains an unwanted pregnancy because that demand places her in a state of involuntary servitude. Involuntary servitude would put states in breach of international human rights law (Article 8 of International Covenant on Civil and Political Rights). Furthermore, we argue that the fact that a life may be forfeit when a woman withdraws her service is no basis for enforcing the servitude. We draw on the 13th Amendment of the US Constitution as an example to extend the argument and highlight the need to test involuntary servitude in international human rights law through mechanisms offered in the international periodic review of member states. This could provide a robust approach to support and strengthen access to safe abortion services.